2013
DOI: 10.1159/000346748
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Prior TURP on Radical Prostatectomy Surgical Margins: A Multicenter Analysis

Abstract: Objective: To analyze positive surgical margins (PSM) after radical prostatectomy (RP) in the overall population and in patients previously treated with transurethral resection of the prostate (TURP). Materials and Methods: 2,408 patients treated with RP for clinically localized prostate cancer (PCa) were consecutively enrolled in 135 departments. We correlated PSM rates and all preoperative, surgical and pathological features. We stratified the site of PSM as unique or multifocal. Moreover, we analyzed differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…In contrast with men without previous TURP, surgeons would perform RP with neurosparring techniques [26]. The results of this data processing are in line with previous meta-analysis studies conducted by Gacci et al in 2013 where there are differences in patients who underwent previous TURP surgery [12].…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In contrast with men without previous TURP, surgeons would perform RP with neurosparring techniques [26]. The results of this data processing are in line with previous meta-analysis studies conducted by Gacci et al in 2013 where there are differences in patients who underwent previous TURP surgery [12].…”
Section: Discussionsupporting
confidence: 82%
“…Consistently, the increasing incidence of BPH and prostate cancer with age further supports this data [6]. Several studies suggest that compared to patients who were previously treated with TURP, patients without any history of TURP procedure has statistically difference margin of localization [3]. Another study suggests that a patient with a history of undergoing TURP procedure might have less satisfactory outcomes regarding operative time, length of stay (LOS), positive margin rate (PMR) and complication rate [7].…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…33 Paul et al 38 studied 52 cases with iPCa after TURP undergoing RP and showed that TURP is not an adverse predictive factor and morbidity is similar to patients who were detected by needle biopsy. Gacci et al 39 showed that Men who treated with TURP before RP presented an overall incidence of positive surgical margin (PSM) similar to those without previous TURP. However, several studies reported higher PSM rates (21.8-34.2%) in patients who underwent latent-RP (LRP) after TURP.…”
Section: Treatmentsmentioning
confidence: 99%